All Days 2014
DOI: 10.4043/24880-ms
|View full text |Cite
|
Sign up to set email alerts
|

Permeability-Dependent Retention of Polymer in Heterogeneous Reservoirs

Abstract: Polymer retention occurring in porous media induces significant mobility reduction as well as poor sweep efficiency. In the heterogeneous reservoir, it is very complicated and difficult to analyze performance of polymer due to permeability-dependent retention. Among various mechanisms of retention, mechanical entrapment of polymer affects mainly the propagation of injected polymer solution by forming macromolecular polymer plugging into pore throats, especially occurring in low permeability zone. Besides, poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Heterogeneities in petrophysical properties, especially in permeability, can result in these adsorption properties varying significantly within a reservoir system. For example, the adsorbed polymer induces greater resistance to flow in the low permeability layers than in the high permeability layer [14,19,20]. According to the Jewett and Schurz experimental works [9], they found that no accurate correlations between residual resistance factors and permeability were available.…”
Section: Heterogeneity In Permeability Versus Polymer Adsorptionmentioning
confidence: 99%
“…Heterogeneities in petrophysical properties, especially in permeability, can result in these adsorption properties varying significantly within a reservoir system. For example, the adsorbed polymer induces greater resistance to flow in the low permeability layers than in the high permeability layer [14,19,20]. According to the Jewett and Schurz experimental works [9], they found that no accurate correlations between residual resistance factors and permeability were available.…”
Section: Heterogeneity In Permeability Versus Polymer Adsorptionmentioning
confidence: 99%
“…Polymer retention is the phenomenon of losing polymer molecules into the porous medium by various mechanisms, including the adsorption of polymer molecules onto the rock due to dominant binding forces, mechanical entrapment of polymer molecules in small pores, and hydrodynamic retention due to the varying flow rates (Grattoni et al 2004;Choi et al 2014;Zhang and Seright 2015). Several factors influence polymer adsorption, including polymer type, rock surface properties, and connate/injection water properties (Afolabi et al 2019;Ahsani et al 2021).…”
Section: Introductionmentioning
confidence: 99%